2012
DOI: 10.1002/jsfa.5691
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of low‐fat chicken nuggets: effect of common salt replacement and added bottle gourd (Lagenaria siceraria L.)

Abstract: The results suggest that low-salt, low-fat and high-fibre chicken nuggets can be developed with the use of a salt substitute blend and bottle gourd without affecting their acceptability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 37 publications
(38 reference statements)
10
20
0
Order By: Relevance
“…Verma et al (2013) reported similar findings in sheep meat nuggets on incorporation of guava powder. A similar decrease in emulsion stability was also reported by Banerjee et al (2012), Verma et al (2012a), (2012b) and (2010) in various meat products.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Verma et al (2013) reported similar findings in sheep meat nuggets on incorporation of guava powder. A similar decrease in emulsion stability was also reported by Banerjee et al (2012), Verma et al (2012a), (2012b) and (2010) in various meat products.…”
Section: Resultssupporting
confidence: 87%
“…Additionally lower emulsion stability might have resulted in the loss of moisture content while cooking. Similar decrease in cooking yield was also reported by Verma et al (2013) in sheep meat nuggets on incorporation of guava powder, Banerjee et al (2012) in goat meat nuggets on incorporation of broccoli powder extract, Verma et al (2012a) in low-fat chicken nuggets on sodium chloride replacement and incorporation of bottle gourd and by Verma et al (2012b) in low-fat chicken nuggets on sodium chloride replacement and added chickpea hull flour. Similar decrease in the cooking yield was also reported by Verma et al (2010) in low-fat chicken nuggets on sodium chloride replacement and apple pulp inclusion and Devatkal et al (2004) in buffalo loaves on incorporation of carrot and potato.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Kumar and Sharma (2004) also reported similar results in pork patties. Verma et al (2012) also observed significant reduction in cholesterol content of low fat chicken nuggets. A reduction of 50-59 % in cholesterol was also reported in carrageenan added low fat beef frankfurters as compared to control by Candogan and Kolsarici (2003b).…”
Section: ±057mentioning
confidence: 65%